Broodstock exposure to warming and elevated pCO2 impairs gamete quality and narrows the temperature window of fertilisation in Atlantic cod. Issue 4 (21st July 2022) - Dahlke, Flemming; Puvanendran, Velmurugu; Mortensen, Atle; Pörtner, Hans‐Otto; Storch, Daniela
Abstract: Impacts of global warming and CO2 ‐related ocean acidification (OA) on fish reproduction may include chronic effects on gametogenesis and gamete quality, as well as acute effects on external fertilisation. Here, temperature thresholds and OA‐sensitivity of gametogenesis and fertilisation were investigated in Atlantic cod, Gadus morhua . Three broodstock groups of farmed cod (FC 1–3) were exposed for 3 months to three maturation conditions (FC 1: control, 6°C/400 μatm CO2 ; FC 2: warming, 9.5°C/400 μatm; FC 3: warming and OA, 9.5°C/1100 μatm). In addition, a broodstock group of wild cod (WC) was kept at control conditions to compare the acute temperature window of fertilisation with that of farmed cod (FC 1). Fertilisations were conducted in a temperature‐gradient table at 10 temperatures (between −1.5 and 12°C) and two CO2 levels (400/1100 μatm). In FC 1 and WC, fertilisation success was relatively high between 0.5°C and 11°C ( T Range of c. 10.5°C), indicating similar gamete quality in farmed and wild broodstocks kept at control conditions. Exposure of farmed broodstocks to warming (FC 2) and the combination of warming and OA (FC 3) impaired gamete quality, causing a reduction in fertilisation success of −20% (FC 2) and − 42% (FC 3) compared to FC 1. The acute temperature window of fertilisation narrowed from FC 1 ( T Range = 10.4°C) to FC 2 ( T Range = 8.8°C) and FC 3 ( T Range = 5.9°C). Acute effects of CO2 on fertilisation success were not significant. This study demonstrates potential climate change impacts on gametogenesis and fertilisation in Atlantic cod, suggesting the loss of spawning habitat in the coming decades.